1999
DOI: 10.1097/00005373-199901000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Management of Blunt Splenic Trauma in Patients Older than 55 Years

Abstract: Observation of the elderly patient with blunt splenic trauma has an acceptable failure rate of 17%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 14 publications
0
19
1
Order By: Relevance
“…41,42 Similar findings were noted in the 10 geriatric patients who, because of associated premorbid factors may not appear to be ideal candidates for nonoperative management but, with close monitoring, the outcome can also be successful. 43 A point of controversy that still exists in the literature is the appropriateness of nonoperative management of solid organ injuries in patients who have an altered mental status. Pachter and colleagues recommended that the patients have an "absence of peritoneal signs when neurologically intact and not under the influence of drugs or alcohol".…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Similar findings were noted in the 10 geriatric patients who, because of associated premorbid factors may not appear to be ideal candidates for nonoperative management but, with close monitoring, the outcome can also be successful. 43 A point of controversy that still exists in the literature is the appropriateness of nonoperative management of solid organ injuries in patients who have an altered mental status. Pachter and colleagues recommended that the patients have an "absence of peritoneal signs when neurologically intact and not under the influence of drugs or alcohol".…”
Section: Discussionmentioning
confidence: 99%
“…For example, Barone and colleagues studied 33 patients (mean age, 72±10 years) who were divided into two groups, 10 patients who underwent immediate exploration and 23 patients who underwent observation. 23 Although observation of patients with blunt splenic injury failed in four of the 23 patients, there were no patient deaths related to the method of management of the splenic injury and hence they concluded that the failure rate of 17% was acceptable. Another study that supports the success of nonoperative management of splenic injury in this age group is Cocanour’s retrospective review of 375 patients over a five-year period.…”
Section: Risk Factors For the Failure Of Nonoperative Managementmentioning
confidence: 98%
“…Several historic predictors of failure of conservative management, including complex splenic injuries [24], older age [25], pre-existing splenic pathology [26] or blood transfusion requirement are no longer universally accepted as reasons to avoid NOM of splenic trauma.…”
Section: Splenic Injuriesmentioning
confidence: 99%
“…Patients with a high grade injury are at greatest risk of failure of observational management (up to 70%) [25,26,30,38] and are at greatest risk of delayed operative intervention [14]. The need for transfusion of greater than 1 unit of blood is another independent risk factor for failure of observation [27,30] and haemodynamic instability will also determine further treatment as is discussed later.…”
Section: Splenic Injuriesmentioning
confidence: 99%